The Effect of Ramadan Intermittent Fasting on Cognitive Work Performance: A Natural Experimental Approach - Prasetyo, Ridwan Aji Budi; Nurwanti, Ratri; Alhad, Muhammad Afif (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2024)
This study aims to investigate the effect of Ramadan intermittent fasting on cognitive work performance using a more natural approach. To achieve the objective of this study, a natural experimental approach was employed by incorporating a pretest-posttest control group design. A forward-type Digit Span Test (DST) was utilized as the measure of the cognitive work performance and was administered to participants twice, before and during Ramadan, with one-month gap between the tests. Two hundred and sixty-seven participants were naturally grouped into fasting and non-fasting groups according to their report during Ramadan session and into morning and afternoon periods, or AM and PM hours, according to their module scheduling. The results of the analyses suggest that the cognitive work performance of the fasting participants during the PM hours is better, after controlling the DST scores before Ramadan. The study also concludes that the cognitive work performance of the fasting participants between AM and PM hours does not differ. This result could be explained using the perspectives of post-lunch performance dip and the beneficial effect of breakfast. Methodological limitations and potential practical implementation of this study are also discussed.